Role of Pulmonary Evaluation in Diagnosis of Neurosarcoidosis - Kingah, Pascal; Alam, Muhammad; Chugh, Karan; Kamholz, John; Samavati, Lobelia (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Neurosarcoidosis is a serious extra pulmonary manifestation of sarcoidosis. Its presentation ranges from peripheral or cranial neuropathy to central nervous system dysfunction. It can mimic stroke or multiple sclerosis. Due to the variation in clinical presentation, diagnosis is difficult and often delayed. Objective: Determine the proportion of patients with neurosarcoidosis who have positive findings on chest CT, lung biopsy or lymph node biopsy. Methods: Retrospective study at the Sarcoidosis and Interstitial Lung Disease Center at Wayne State University–Detroit Medical Center in Detroit, MI. Medical records of 424 patients were reviewed and 69 patients with neurosarcoidosis identified. Results: We found that most patients diagnosed with neurosarcoidosis had normal PFT values except for reduction in DLCO. However, we also found that 71% of the patients had abnormal findings on chest CT consistent with sarcoidosis.  Additionally, 57% of the patients had non-caseating granuloma on hilar lymph node biopsy. Conclusion: Patients with neurosarcoidosis may not have any pulmonary symptoms. However, they are most likely to have abnormal chest CT, hilar lymphadenopathy and reduction in DLCO.  These data suggest that pulmonary evaluation is warranted in patients who are suspected to have neurosarcoidosis.